Bone histology of Azendohsaurus laaroussii: Implications for the evolution of thermometabolism in Archosauromorpha. Issue 2 (1st May 2019) - Cubo, Jorge; Jalil, Nour-Eddine
Abstract: This paper is aimed at constraining the phylogenetic frame of the acquisition of endothermy by Archosauromorpha. We analyzed the bone histology of Azendohsaurus laaroussii . Stylopodial and zeugopodial bones show three tissue types: (1) avascular lamellar zonal bone formed at low growth rates; (2) a scaffold of parallel-fibered bone containing either small primary osteons or simple vascular canals; and (3) fibrolamellar bone formed at high growth rates. We used quantitative histology to infer the thermometabolic regime of this taxon. We define endothermy as the presence of any mechanism of nonshivering thermogenesis that increases both body temperature and resting metabolic rate. Thus, estimating the resting metabolic rate of an extinct organism may be a good proxy to infer its thermometabolic regime (endothermy vs. ectothermy). High resting metabolic rates have been shown to be primitive for the clade Prolacerta –Archosauriformes. Therefore, we inferred the resting metabolic rates of A. laaroussii, a sister group of this clade, and of 14 extinct related taxa, using phylogenetic eigenvector maps. All the inferences obtained are included in the range of variation of resting metabolic rates measured in mammals and birds, so we can reasonably assume that all these taxa (including Azendohsaurus ) were endotherms. A parsimony optimization of the presence of endothermy on a phylogenetic tree of tetrapods shows that this derived character state was acquired by the last common ancestor of the clade Azendohsaurus –Archosauriformes and that there is a reversion in Crocodylia.